Adoption of social media by travel agencies in Malaysia - Parvej, Khandaker Masud (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
Social media has become a trend for youngster and business partner today. Therefore, this research had been carried out to encourage travel agencies to adoption of social media as new business platform to further improve their business. This is because 92% of marketers declared that social media marketing is important to increase growth for businesses. Some of the entrepreneur still prefer offline business because they think that traditional marketing still remain as rival for social media marketing. To determine why travel agents can influence to adopt social media, several factors like relative advantage, compatibility, complexity, trialability and observability has been adoption to become a framework. Data has been collected through convenience sampling method where printed questionnaire distributed to travel agents in Klang Valley area, in Malaysia. About 220 questionnaires were distributed in the selected area and received 210 questionnaires. After screening all 210 questionnaires only 200 respondents are eligible to analysis. The results of this study indicated that four Hypothesis namely relative advantage, compatibility, trialability and observability was supported, and the only complexity was not supported. This research provides further information for researcher when they want to conduct similar research in the future. The identified constructs in this paper are inspired from the Roger diffusion of innovation theory.